Attribution Des Noms Et Pratiques En Santé Materno-Infantile : Approche Socio-Anthropologique Des Enfants Sacrés En Pays Abouré Et Baoulé De Cote d’Ivoire - N’Goran, Sylvie; Oga, Maxime (European Scientific Journal, ESJ, 2017)
The birth of a child is considered as a joyous event and comes along with celebrations and festivities according to the tradition of each cultural group. The name given to the new-born may be that of a living grandparent, one of the parents, or a friend of the child’s father. However, the name given may also be related to the birth order. The birth of a child, who is a fragile and vulnerable being, gives rise to indispensable rituals that takes into account its rank. These rituals are not only for its survival and development, but also for its socialization and the transformation of its identity. Tradition also involves cultural identity through name assigning in order to protect the child from all kinds of diseases. Moreover, traditional practices regarding the issue of child health serves as forms of protection, humanization, and integration of the child into the society. What about the Aboure and N’Zipkly people? From a comprehensive perspective on the specificity of the names given from birth, this study aims to grasp the plausible influences on child health based on the relationships between the child and his name as perceived by the Abouré and N’Zipkly people. To achieve this, we asked ourselves the following questions: Why does a name has a significant influence on the health of the newborn? What is the relationship between child health and name? What are the socio-cultural practices of sacred children? Furthermore, there were various questions that led to data collection by observing activities and practices related to sacred children. The data collection was done using interview guides for mothers with children aged 0 to 5 years, grandparents, and traditional therapists.